Clinical Features and Treatment Outcomes of Immune Thrombocytopenic Purpura in Infants: A Single Center Retrospective Study - Sang Jun Sohn; Kyung Mi Park; Eu Jeen Yang; Young Tak Lim (The Korean Society of Pediatric Hematology-Oncology, 2019)
Background : : Immune thrombocytopenic purpura (ITP) in children less than one year of age is less well characterized compared to ITP in toddlers and school-age children. Since children of different ages may have differing clinical courses, better delineation of the natural history of ITP in infants is needed. Methods : : We retrospectively reviewed the admission records of 248 consecutive pediatric patients between 1 month and 15 years of age who were admitted and treated for acute ITP at Pusan National University Children's Hospital from 2009 through 2017. All patients less than 1 year of age were identified and enrolled in this study. We investigated their demographics, clinical features, laboratory examinations, response to treatment, and long-term outcomes and made a comparison to those of children aged 1 to 10 years of age. Results : : Ninety nine infants were identified. Male to female ratio was highest in infants and decreased with age. Seventy nine (79.8%) of the 99 infant were found to be under 6 months old. The median platelet counts at diagnosis was 6×109/L. Minor bleeding (bleeding score 0-2) was significantly dominant in infant compared to older subjects. Eighty two (96.5%) out of 85 patients achieved complete remission after initial intravenous immunoglobulin (IVIG) treatment. The relapse rate after initial CR was significantly lower than older ages (P=0.003). The platelet count after IVIG treatment in infant showed more rapid response compared to older subjects (P=0.04). Follow up information at 12 months was available for 70 infants. Chronic ITP at 12 month was seen less frequently in infants than in children 1 to 10 years of age (1.4% vs. 20.2%, P<0.001). Conclusion : : Infants with acute ITP respond more favorably to IVIG treatment and are less likely to develop chronic ITP compared to children 1 to 10 years of age.